Pemilihan Kepala Desa Perspektif Mohammad Hatta: (Program Studi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Pemikiran Islam, 2020)
This research was conducted in Simpang Tanjung Village, Belimbing District, Muara Enim Regency with the aim of knowing the Village Head Election Perspective of Mohammad Hatta. Mohammad Hatta is a true democrat, big-hearted, a fighter to defend the people. According to Mohammad Hatta, politics is politics that emphasizes the sovereignty of the people, the sovereignty of the people here means that the power for a government of a nation and a state rests with the people where the people are sovereign, have the power to determine how to be governed. This research uses a qualitative approach with descriptive research type. The subjects of this study were the Head of Simpang Tanjung Village, Village Secretary, Head of Rw, Religious Leaders, and Simpang Tanjung Village Residents. Data were collected through interview techniques, observation, documentation. The results of this study indicate that the election of the village head expected in Muhammad Hatta's thought is an election that is democratic, fair, and does not conflict with norms and religion. However, the process of electing the village head of Simpang Tanjung village still has money politics, dawn attacks, bribes, and promises about the progress and welfare of the village community. However, not all village head candidates use the above unsavory methods. On the other hand, there are still candidates for village heads who show attitudes and behaviors that are appropriate to become the new village head.